Tonlesapia amnica, a new species of dragonet (Teleostei: Callionymidae) from the Mekong delta HEOK HEE NG (Singapore) & WALTER J. RAINBOTH (USA) - Ng, Heok Hee; Rainboth, Walter J. (Zootaxa, 2011)
Tonlesapia amnica, a new species of dragonet lacking a first dorsal fin, is described from the Mekong River delta in southern Vietnam. It can be distinguished from its sole congener, T. tsukawakii, in having the infraorbital canal extending beyond (vs. not reaching) ventral margin of orbit, a more slender body (7.2–13.5% SL vs. 14.3–15.0) and caudal peduncle (4.4–5.2% SL vs. 5.1–6.3), a smaller eye (6.5–8.3% SL vs. 8.7–9.2) and more dorsal-fin rays (9–10 vs. 8).